The Relationship between Smooking Intensity and VO2MAX Among Students At the Indonesian Institute Of The Arts Yogyakarta - Rahma, Aulia; Khotimah, Siti (FISIO MU: Physiotherapy Evidences, 2026)
Introduction: As agents of change, university students require two supporting factors, namely physical fitness and academic performance. Students with low VO₂MAX values experience decreased learning outcomes and low levels of fitness, with one influencing factor being smoking habits. Smoking habits affect cardiovascular endurance due to the nicotine content in cigarettes, which can damage the lungs. This study aimed to investigate the relationship between smoking intensity and VO₂MAX among students. Methods: This correlation study employed an analytical observational method with a cross-sectional design. Purposive sampling was used to select 40 participants. The Cooper Test was used as the measurement tool. Data were analysed using the Spearman rank correlation. Results: The analysis of the relationship between smoking intensity and VO₂MAX using the Spearman rank test yielded a p-value of 0.01 (p < 0.05). This result shows a significant relationship between smoking intensity and VO₂MAX values. The correlation coefficient was -0.741, which indicates a strong statistical relationship between the variables. Conclusion: There is a relationship between smoking intensity and Maximum Oxygen Consumption (VO₂MAX) values among students.